The effect of social media influencer on youth online buying behaviour in Klang Valley - Goh, Pieh Ling (2024)
Nowadays, many companies use social media influencer marketing as their marketing strategy. This is because the rise of social media platforms has led to many people find the product recommendation and solution through social media influencers. Many companies will find the social media influencer to endorse their products. Therefore, it is important for company to know the effect of social media influencers on youth online buying behaviour. This research aims to study the effect of social media influencer on youth online buying behaviour within the context of social media influencer marketing in Klang Valley. The independent variables in this research are subjective norms, identification with influencer, and perceived social proof which is based on the theory of planned behaviour and social influence theory. The target population of this research is the youth aged between 15 to 30 years old. Data were collected from 199 youth in Klang Valley and their data were analysed by using Statistical Package for Social Sciences (SPSS). The findings revealed that the identification with influencer and perceived social proof have a significant relationship on youth online buying behaviour within the context of social media influencer marketing in Klang Valley. Overall, this research help to better understand on youth buying behaviour within the context of social media influencer marketing in Klang Valley.